Effects of verbal knee alignment instructions on knee kinematics, kinetics and the performance of a single-leg jump in female adolescent soccer players. (3rd March 2020) - Grooten, Wilhelmus Johannes Andreas; Karlefur, Oskar; Conradsson, David
Abstract: Background: Little is known about the effects of verbal instructions on the technique and performance of sports-related tasks. The aim of this study was therefore to investigate the acute effects of knee alignment instructions on knee kinematics and the performance of a single-leg jump in female adolescent soccer players. Methods: Twenty-eight adolescent female soccer players completed three blocks of 15 single-leg jumps. The participants were randomised to an experimental group receiving verbal instructions focussing on proper knee alignment (the avoidance of knee valgus) or to a control group only receiving instructions on task execution. Outcomes were knee kinematics (flexion and valgus angles) and jump performance (number of incorrect trials and contact time). Results: The experimental group demonstrated 36% less knee valgus and 11–13% greater knee flexion compared to the control group. While jump performance remained unchanged in the experimental group over the course of the experiment, the control group demonstrated a 20% decrease in the number of incorrect trials and a 25% reduction in contact time over the course of the experiment. Conclusions: The present results indicate that verbal instructions accentuating proper knee alignment benefit knee kinematics but not jump performance in adolescent female soccer athletes.